Colombia : Staff Report for the 2006 Article IV Consultation and the Third and Final Review Under Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2006)
Since 1999, economic policies have sought to place the country on a path of sustainable growth, which would help reduce unemployment and poverty. The authorities have begun to address the risk of overheating, although demand policies may need to be tightened further. Monetary policy will be aimed at lowering inflation further to 2-4 percent over the medium term. The authorities' medium-term fiscal plan will strengthen the economy and build resilience. IMF staff recommends completion of the third and final review.